Truncated V-fractional Taylor's Formula with Applications - Sousa, José Vanterler da Costa; Oliveira, Edmundo Capelas de (Trends in Computational and Applied Mathematics, 2018)
In this paper, we present and prove a new truncated V-fractional Taylor's formula using the truncated V-fractional variation of constants formula. In this sense, we present the truncated V-fractional Taylor's remainder by means of V-fractional integral, essential for analyzing and comparing the error, when approaching functions by polynomials. From these new results, some applications were made involving some inequalities, specifically, we generalize the Cauchy-Schwartz inequality.